Pengembangan Buku Ajar Bioteknologi Berbasis Science, Technology, Engineering, Math (STEM) untuk Meningkatkan High Order Thinking Skill (HOTS) Mahasiswa - Aldila Wanda Nugraha; Rohmatus Syafi'ah (Department of Biology Education, Faculty of Education and Teacher Training, UIN Sunan Gunung Djati Bandung, 2021)
This research was conducted with the purpose to: (1) Develop a STEM-based textbook for molecular biology technique material in introductory biotechnology courses (2) Increase students' HOTS (higher-order thinking skill) capabilities on molecular biology technique materials in biotechnology introductory courses. The method used in this study is Educational Research and Development (R&D). The stages are outlined in the 4D model which includes: (1) Define; (2) Design ; (3) Development; and (4) dissemination. Based on the analysis of data on the STEM-based Biotechnology textbook validation questionnaire by media experts and teaching materials, as well as education and learning experts obtained an average score of 88.45 and 83.6 which are included in the valid category. The results of the implementation of trials on students obtained 88.8 results, indicating that the product produced is valid and good enough to be used as teaching material.